Virology methods manual - Mahy, B. W. J. (Brian W. J.); Kangro, Hillar O. (Academic Press, 1996)
The Virology Methods Manual is a comprehensive source of methods for the study, manipulation, and detection of viruses. Edited by Brian Mahy and Hillar Kangro, this work describes the most up-to-date, definitive techniques, provided by experts in each area, and presented with easy-to-use, step-by-step protocols. This new manual will satisfy the needs of virologists and all those working with viruses who need a practical guide to methods that work! Key Features * Provides up-to-date techniques by experts worldwide * Presents common, step-by-step protocols in an attractive, easy-to-use fashion * Contains useful appendices including virus taxonomy, metabolic inhibitors, and Bio-safety in the virology laboratory.